The relationship between programmed cell death and vascular calcification - Zheng, Jie; Lin, Zhengjie; Zhong, Xiaolin; Liu, Jianghua (Frontiers in Cardiovascular Medicine, 2025)
Vascular calcification (VC) is a pathological condition closely associated with a range of cardiovascular diseases, including atherosclerosis (AS), hypertension, vascular injury, and diabetic angiopathy. Programmed cell death, encompassing apoptosis, autophagy, pyroptosis and ferroptosis, plays a pivotal role in the progression of VC. These cellular processes are intricately regulated by multiple signaling pathways, such as the Wnt/β-catenin and NF-κB pathways, among others. A deeper understanding of the roles and underlying mechanisms of programmed cell death in VC could offer valuable insights for the development of innovative therapeutic strategies targeting cardiovascular diseases.